Development of DC Motor Controlled Automated Manual Transmission (AMT) (Global Journals of Research in Engineering, 2014)
Automated Manual Transmission (AMT) has been the#xD;best competitive solution to address the problem of increasing fuel prices and to meet the emission norms. Automotive world today mostly uses Automated Manual Transmission (AMT) based on hydraulic actuators. Hydraulic actuators are costly,#xD;complex in design, bulky and invite drastic design changes in existing gearbox. AMT system which is low cost and fuel efficient has been developed using DC motor controlled electro mechanical linear actuators. The AMT system consists of#xD;three electro-mechanical linear actuators, one for clutch and two for gear shift actuations which are controlled by Transmission control unit (TCU). The wear of synchronizers can be easily taken care by reprogramming the stroke lengths of linear actuators. This system can be retro fitted in vehicle with#xD;existing manual gearbox and involve minor design changes. The focus of paper is to introduce the system developed.
Keywords: actuator; AMT; automated manual transmission; transmission